Visual demand evaluation methods for in-vehicle interfaces - Pettitt, Michael Andrew (2008)
Advancements in computing technology have been keenly felt in the automotive industry. Novel in-car systems have the potential to substantially improve the safety, efficiency and comfort of the driving experience. However, they must be carefully designed, so their use does not dangerously distract drivers from fundamental, safety-critical driving tasks. Distraction is a well-established causal factor in road accidents. A concern is that the introduction of new in-vehicle technology may increase exposure to distraction, and lead to an increase in distraction-related accidents. The range of systems often termed In-Vehicle Information Systems (IVIS), encompassing navigation and entertainment systems, in-car email and Internet, are the focus of this thesis, since they are commonly associated with long tasks that are not considered fundamentally relevant to driving.